Clinical Sports Medicine - Kalski L; 2; Bauerecker IL; 2; Jarius L; Hafermann L; Wolfarth B; 2 (Dynamic Media Sales Verlag, 2023)
Purpose: The COVID-19 pandemic affects society on a global scale in many ways. In Germany, various social and leisure facilities such as schools, sports clubs and gyms had to be closed due to lockdowns. The impact of these closures on sports behavior in children and adolescents is still insufficiently explored.Methods: To address that, we conducted a survey among 51 athletes, asking them retrospectively about their training, their competitions, their training motivation, and their concerns about the future.Results: The athletes, aged 9-20 years, (66.7% female, 43.1% performance sports) reported the lowest hours of exercise during the first lockdown: 5 (9.8%) children mentioned 0h per week and 31 (60.8%), 1-5h per week. Recreational athletes were more affected than performance athletes. Before the COVID-19 pandemic, 8 (15.7%) of all athletes had motivational problems regarding their training in contrast to 25 (49.0%) during the lockdowns. 19 (37.3%) of the athletes reported that the pandemic will have an impact on their career regardless of a COVID-19 infection.Conclusion: Sport faded into the background during this challenging time, athletes sports behavior has been affected in many ways. It is important that children and adolescents are quickly enabled to return to sport, as the health benefits speak for themselves.Key Words: SARS-CoV-2, Questionnaire, Young Athletes, Competitive Sports, Physical Activity, Training Motivation